2017
DOI: 10.1016/j.hrthm.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of remote monitoring of cardiac implantable electronic devices: Results of the Health Economics Evaluation Registry for Remote Follow-up (TARIFF) study

Abstract: RM of patients with cardiac implantable electronic devices (CIEDs) is cost saving from the perspectives of the HCS, patients, and caregivers. Introducing appropriate reimbursements will make RM sustainable even for the provider, i.e. the hospitals which provide the service and encourage widespread adoption of RM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 23 publications
2
44
3
Order By: Relevance
“…In addition, the study did not include health care provider expenses, which could impact total cost savings offered by telemedicine, such as the cost of telemedicine units (both new units and replacement of outdated or broken units), staff hourly wages (physicians, licensed nurses, IT support staff), Internet usage, and telecommunications connectivity. Previous studies have found that despite these costs to implement and maintain a telemedicine program, from the health care system perspective, telemedicine programs still remain cost-effective [22][23][24], although this may vary by specialty [25]. If additional data were made available, a more accurate picture of the environmental impact of telemedicine could be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study did not include health care provider expenses, which could impact total cost savings offered by telemedicine, such as the cost of telemedicine units (both new units and replacement of outdated or broken units), staff hourly wages (physicians, licensed nurses, IT support staff), Internet usage, and telecommunications connectivity. Previous studies have found that despite these costs to implement and maintain a telemedicine program, from the health care system perspective, telemedicine programs still remain cost-effective [22][23][24], although this may vary by specialty [25]. If additional data were made available, a more accurate picture of the environmental impact of telemedicine could be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-utility and cost-effectiveness analyses help to quantify the value of new interventions, informing both medical decision making and public policy [24,25]. Although in the last years, economic assessments of CIEDs have increased [26][27][28][29][30][31][32][33][34], the number of cost-utility analyses used to assess outcomes in terms of utility or quality-adjusted life years (QALYs) is scarce [35], especially in PM devices [36,37], needing more health economic studies to determine the value (the relationship between additional QALYs achieved and additional costs incurred) of systematic remote monitoring in users with pacemakers.…”
Section: Introductionmentioning
confidence: 99%
“…By applying the inclusion and exclusion criteria, the number of studies were further reduced to 37. After the full texts of 37 potentially relevant studies had been reviewed, 3 articles met the selection criteria finally, as described in Figure 1, and were included into this study (Zanaboni et al, 2013;Ricci et al, 2017; Lopez-Villegas, Catalan-Matamoros, Robles-Musso, Bautista-Mesa, & Peiro, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Zanaboni, et al found "that chronic HF patients wearing ICD/CRT-D followed with remote monitoring gained 0.066 QALYs more than those in the standard arm over the 16-month study period" (Zanaboni et al, 2013). Ricci et al reported 0.02 QALYs more were obtained from Remote Monitoring Group than Standard Care Group (Ricci et al, 2017). And Lopez-Villegas, et al put the outcome that "patients in the TM group gained 0.09 QALYs more than those in the HM group" (Lopez-Villegas et al, 2018).…”
Section: Study Outcomesmentioning
confidence: 99%